Berberis thunbergii (Berberis thunbergii DC.) as a little-known representative of the genus Berberis L. in pharmacy - chemical composition, biological activity and perspectives of application - Anna Och; Karolina Orzechowska (Polish Pharmaceutical Society, 2024)
Abstract: The subject of the review was data on the Berberis thunbergii species, which is relatively poorly known, both in terms of chemical composition and biological activity, and berberine, a currently intensively researched alkaloid. The subject of the review was also a comparison with other species belonging to the genus Berberis. The genus Berberis includes approximately 580 species of shrubs, relatively few of which have been evaluated for chemical composition and biological activity. The aim of the work was to organize the current knowledge about the chemical composition and biological activity of the species, which is known mainly only as a popular garden plant. The aim of the work was also to assess the prospects of herbal raw material in pharmacy as a source of berberine. The scientific databases SCOPUS, PubMED, PubChem, Google Scholar and ClinicalTrialsGov were reviewed using keywords: anticancer activity of Berberis thunbergii, biological activity of Berberis thunbergii, Berberis in traditional medicine and berberine. About a hundred articles were searched and data providing current knowledge about the species were selected. Berberis thunbergii is a valuable alkaloid raw material. It contains m.in. berberine, an important alkaloid that is currently attracting considerable interest and has increasing prospects in pharmacy. This compound offers great hope for patients, but its use is still limited due to low bioavailability. Hence, research on new forms of administration is very important. There is a great need for further research on the content of active substances in extracts from individual parts of Berberis thunbergii and their pharmacological effects in many yet unexplored areas, because plant extracts are often characterized by the phenomenon of synergism, which may be crucial in the case of problems with the pharmacokinetics of berberine and the current need to refine the form of its her application. Berberis thunbergii is a valuable herbal raw material, especially due to the content of berberine as well as other biologically active alkaloids, which should be further investigated, especially in terms of anticancer, antidiabetic and chemopreventive activity.